Identifying the deployment area of illegal armed formations likely location after establishing the preliminary contact at the outer blocking line - Obryadin, V. V.; Panchenko, V. Yu.; Rozanova, L. V. (Honor and Law, 2019)
The mathematical model of the identifying of the likely location of the deployment area of illegal armed formations that advance to the terrorist-action area after establishing the preliminary contact with them at distant reconnaissance line is given.